Potensi Limbah Industri Pengolahan Kedelai Sebagai Bahan Suplementasi dalam Ransum Ternak Domba - Eka Handayanta (Caraka Tani: Journal of Sustainable Agriculture, 2003)
Efficacy of livestock is very determined by feeds. High or low livestock production depending on amount and feeds quality given, either in sheep production. Sheep will not be optimal production if only given by grass, so it needed supplement by other feeds materials contains high nutrition materials like legume and concentrate.By giving concentrate to sheep, it can improve growth, flesh production and also crabbed weight. But used of concentrate require to be considered. Because it’s costly is price so that can cause the expense of feeds become high. Therefore require to be searched by alternative materials which in big supply, easy to get, its price cheap but can support high production, and have no or a little competition with use for the livestock of other livestock for example poultry and ruminant. One of the materials is industrial disposal processing of soy. At processing of soy become Tempe or ketchup, it is produce waste in the form of Tempe dregs, Tofu dregs and ketchup dregs. Seen from its nutrient content, especially harsh protein and energy, the dregs have potency to be used as livestock feeds, especially upon which supplementation in feeds of sheep livestock.